Taking drugs during pregnancy. How safe are the unsafe? - Koren, G. (2001)
QUESTION: I prescribed misoprostol to one of my patients with a peptic ulcer. When she found out she was pregnant while on the drug, both she and, admittedly, I were very scared to learn that the drug is teratogenic in that it causes Möbius syndrome. How great is the risk? ANSWER: Very small. Although women who use misoprostol during the first trimester have a 30-fold higher risk of having babies with Möbius syndrome, the malformation is so rare that, even if you see 1000 women who took misoprostol during embryogenesis, you might not see a single child with the syndrome. It is crucial to explain the size of the risk; otherwise women tend to believe the risk is huge even when, in fact, it is hardly measurable.